Three dimensional finite element method applied to study the penetration of electromagnetic fields in cavities. - Ladd, Darcy N. (University of Ottawa (Canada), 1990)
A three dimensional formulation of the finite element method was developed to solve the electromagnetic field distribution in an arbitrary region containing conducting and dielectric materials when the tangential magnetic field was known at the boundaries. The formulation was developed using a three component vector magnetic potential and a scalar electric potential. The displacement current as well as the conduction current term was accounted for. The region of interest was discretized using eight node isoparametric hexahedrons and the potential functions were defined using linear first order basis functions. The frequency domain finite element method program was validated by comparison with closed form solutions for simplified geometries. The algorithm proved to have a convergent solution when solving the diffusion of electromagnetic fields into conducting hollow and solid structures without apertures. The penetration of a steady-state electromagnetic field through an aperture into a simple cavity was analyzed with the 3-D FEM program. The diffusion of a step-impulse magnetic filed into a conducting slab was solved directly in the time domain with a time domain finite element program. Conclusions were drawn on the feasibility of using the finite element method as part of an EMI/EMC CAD package.
Keywords: Engineering, Electronics and Electrical.